MENINGKATKAN KINERJA PROGRAM STUDI DENGAN MENGEMBANGKAN SISTEM MANAJEMEN MUTU ISO 9000: MENGAPA PERLU DAN BAGAIMANA MELAKUKANNYA? - Juliani Dyah Trisnawati; Muhammad Rosiawan (Journal of Management and Business, 2002)
In several analysis about the roles and function of a program study in the future that a main roles of education is quality. Program Study that can not keep their quality will be lose in the competition, and make the community not survive in the 21st era.The Program Study has responsibility in quality of realization "tridharma" (Learning, Research and Public Service). That is the reason why the program study should has Quality Management System (QMS) to meet and exceed the stakeholder requirement. The successfully of Manufacturing industry and Service industry get standard ISO 9000 as a Management System can be adopted by program study to improve education quality.This paper describes the important of Quality Management System and the implementation on the program study in order to increase the performance of program study.